Bentuk Tindak Tutur Ilokusi dalam Program Ini Talk Show NET TV - S, Siti Nurkhalizah; Simpen, I Wayan; N Widarsini, Ni Putu (Humanis; Vol 24 No 1 (2020), 2020)
This research is entitled "Illocutionary Speech Acts in This Program Talk Show NET TV". The purpose of this study is to describe the forms of speech acts of illocution and speech strategies contained in this program. This research uses the illocutionary speech act theory proposed by Searle and the speech strategy proposed by Blum-Kulka. At the data collection stage the listening method is used to help with the note taking technique. Stages of data analysis using contextual methods. The stage of presenting the results of data analysis using formal and informal methods. In this program, NET TV Talk Show found five types of illocutionary acts, namely assertive, directive, expressive, commissive, and declarative. There are five data as assertive acts, eleven data are directive, ten data are expressive, four data are commissive, and three data are declarative. This study found three types of speech strategies, namely direct speaking strategies, indirect speaking strategies, and signaling strategies. There are five data are direct speaking strategies, three data are indirect speaking strategies, and two data are signaling strategies.